The SV40 virus enhancer functions as a somatic hypermutation-targeting element with potential tumorigenic activity - Šenigl, Filip; Soikkeli, Anni I; Prost, Salomé; Schatz, David G; Slavková, Martina; Hejnar, Jiří; Alinikula, Jukka (Tumour virus research, 2024)
Simian virus 40 (SV40) is a monkey virus with tumorigenic potential in rodents and is associated with several types of human cancers, including lymphomas. A related Merkel cell polyomavirus causes carcinoma in humans by expressing truncated large tumor antigen (LT), with truncations caused by APOBEC family of cytidine deaminase-induced mutations. AID (activation-induced cytidine deaminase), a member of the APOBEC family, is the initiator of the antibody diversification process known as somatic hypermutation and its aberrant expression and targeting is a frequent source of lymphomagenesis. In this study, we investigated whether AID could cause mutations in SV40 LT. We demonstrate that the SV40 enhancer has strong somatic hypermutation targeting activity in several cell types and that AID-induced mutations accumulate in SV40 LT in B cells and kidney cells and cause truncated LT expression in B cells. Our results argue that the ability of the SV40 enhancer to target somatic hypermutation to LT is a potential source of LT truncation events that could contribute to tumorigenesis in various cell types, thereby linking SV40 infection with malignant development through a novel mutagenic pathway.
Keywords: Humans; Antigens, Polyomavirus Transforming; Enhancer; Tumor Virus Infections; opičí virus SV40; Carcinogenesis; mutace; Somatic Hypermutation, Immunoglobulin; zesilovače transkripce; Tumorigenesis; lidé; zvířata; antigeny transformující polyomavirové; AICDA (aktivací indukovaná cytidindeamináza); polyomavirové infekce; B-lymfocyty; Cytidine Deaminase; Polyomavirus Infections; buněčné linie; SV40; Antigens, Viral, Tumor; AID; Cell Line; somatická hypermutace imunoglobulinových genů; karcinogeneze; B-Lymphocytes; Somatic hypermutation; Enhancer Elements, Genetic; Simian virus 40; AICDA (Activation-Induced Cytidine Deaminase); Animals; cytidindeaminasa; Mutation; Large tumor antigen; antigeny virové nádorové; infekce onkogenními viry